PENGARUH KUALITAS PELAYANAN, KERAGAMAN PRODUK, DAN HARGA, TERHADAP LOYALITAS KONSUMEN PADA CAFÉ KIDY DI KECAMATAN PANJI KABUPATEN SITUBONDO - Fajar Wahyu Prianto (Growth, 2022)
This study aims (1) to determine the effect of service quality, product diversity, price partially affect the consumer loyalty variable (2) to determine the effect of service quality, product diversity, and price have a simultaneous effect on the variable of consumer loyalty (3) to determine the dominant influence among the variables of service quality, product variety, price, which is the most dominant on the variable of consumer loyalty. The method used in this research is quantitative method. The results showed the results of multiple linear regression analysis, namely Y = 1.488E -16+ 0.380X1 + 0.248X2 + 0.263X3 + e. The t-count value for the service quality variable is 3.718. Meanwhile, the value in the 5% distribution table is 1.985, then t-count is 3.718 > t-table is 1.985. Means Ho is accepted or Ha is rejected. This is also reinforced by a significant value of 0.000 > 0.05, meaning that the service quality variable has a partial effect on consumer loyalty. valueT for the variable diversity of products amounted to 3,150. Meanwhile, the value in the 5% distribution table is 1.985, so tcount is 3.150 > ttable is 1.985. means Ho is rejected or Ha is accepted. This is also reinforced by a significant value of 0.002 <0.05, meaning that the product diversity variable has a partial effect on consumer loyalty. The valuecalculated for the price variable is 2.747. The value in the 5% distribution table is 1.985, so tcount is 2.747 > ttable is 1.985. It means that Ho is accepted, Ha is rejected. This is also reinforced by a significant value of 0.007 > 0.05, meaning that the price variable has a partial effect on consumer satisfaction. Simultaneous statistical test or f test shows where the value of farithmetic > ftable 32.554 > 2.47 based on statistical testing using the f test method, where the significant level obtained is 0.000 < 0.05, it can be concluded that the research hypothesis (H2) which states that the quality of service, product diversity, price simultaneously affect consumer loyalty is acceptable.